The role of MICE destination attributes on forming Jordan touristic image - Lim, Khong Chiu; Ananzeh, Omar A. (SAVAP International, 2012)
The attributes of a MICE destination have been shown to have a vital role on the formation of its touristic image. This study examines the role of MICE destination attributes on the formation of the touristic image of Jordan from the perspective of local and international MCE event participants.Amman and the Dead Sea were the study site of this study.Push-Pull theory was utilised to show the importance of pull attributes on forming the destination Image. The relative importance of six attributes of MICE destination is determined.The results revealed significant differences between participants on their perceptions on the importance of MICE destination attributes and that MICE destination attributes influence the destination image formation The findings also provided implications for event planners, event organizers, and other MICE stakeholders in Jordan as well as for academic researchers in MICE tourism.